Controlling Nutritional Status (CONUT) Score as a New Indicator of Prognosis in Patients With Hilar Cholangiocarcinoma Is Superior to NLR and PNI: A Single-Center Retrospective Study - Wang, Ankang; He, Zhenxing; Cong, Peng; Qu, Yueyu; Hu, Tao; Cai, Yu; Sun, Bo; Chen, Hao; Fu, Wenguang; Peng, Yong (Frontiers in Oncology, 2021)
Background: Currently, many nutritional indicators, including controlling nutritional status score (CONUT), can be used to assess a patient's nutritional status and have been reported as reliable predictors of multiple malignancies. However, the value of CONUT score in predicting postoperative outcomes in patients with hilar cholangiocarcinoma has not been explored. In this study, its predictive value will be discussed and compared with the known predictors the neutrophil lymphocyte ratio (NLR) and prognostic nutritional index (PNI). Methods: Preoperative CONUT scores, PNI and NLR levels of 94 Hilar cholangiocarcinoma (HCCA) patients who underwent radical-intent resection of hepatobiliary surgery in our hospital from March 2010 to April 2019 were retrospectively collected and analyzed. They were grouped according to their optimal cutoff value and the prognostic effects of patients in each group were compared respectively. Results: CONUThigh was more frequent in patients with Clavien–Dindo classification of ≥IIIa (P = 0.008) and Bile leakage presence (P = 0.011). Kaplan-Meier curves analyzing the relationship between CONUT, PNI, and NLR values and HCCA patient survival (including total survival (OS) and recurrence-free survival (RFS) showed significant differences between groups (P <0.001). Meanwhile, multi-factor analysis found that Degree of cure, PNI, NLR, and preoperative CONUT score were independent prognostic factors for OS and RFS. The predictive power of CONUT score was higher than that of NLR and PNI based on time-dependent receiver operating Characteristic (ROC) analysis and the net reclassification index (NRI) and integrated discriminatory index (IDI) values (P < 0.05). Conclusion: CONUT score may be of some clinical reference value in evaluating postoperative prognosis of HCCA patients.